2017
DOI: 10.1093/aob/mcx133
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and developmental timing of endosperm failure in post-zygotic isolation between wild tomato lineages

Abstract: The overall results suggest that near-complete hybrid seed failure can evolve fairly rapidly and without apparent divergence in reproductive phenology/biology. While the evidence accrued here is largely circumstantial, early-acting disruptions of normal endosperm development are most probably the common cause of seed failure regardless of the type of endosperm (nuclear or cellular).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(94 citation statements)
references
References 68 publications
3
88
1
Order By: Relevance
“…By generating RNA‐Seq data from developing endosperm in replicated reciprocal crosses, we assessed genomic imprinting in the three wild tomato lineages A , C and P . To maximize power to assess PSE, the parental combinations were chosen based on high inter‐individual molecular polymorphism as well as high seed viability (Roth et al ., ). Biological variation was taken into consideration by using three clonal replicates for each cross, resulting in a total of 18 endosperm samples.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…By generating RNA‐Seq data from developing endosperm in replicated reciprocal crosses, we assessed genomic imprinting in the three wild tomato lineages A , C and P . To maximize power to assess PSE, the parental combinations were chosen based on high inter‐individual molecular polymorphism as well as high seed viability (Roth et al ., ). Biological variation was taken into consideration by using three clonal replicates for each cross, resulting in a total of 18 endosperm samples.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, further investigations are needed to explore patterns of sequence evolution in MEGs and PEGs, for example by repeating such analyses with more individuals and more IGs, preferentially in outcrossing species where IGs are expected to evolve under stronger parental conflict (Brandvain and Haig, ; Haig, ). Data on endosperm growth and seed size in interspecific crosses between these three lineages suggest that lineage P experienced higher levels of parental conflict compared with both A and C (Roth et al ., ), consistent with its higher level of nucleotide diversity (Städler et al ., ; Tellier et al ., ; Beddows et al ., ). Interestingly, we found that conserved IGs tend to have a higher expression in lineage P compared with both A and C (Figure ), possibly reflecting higher levels of parental conflict and mirroring observations in A. lyrata – A. thaliana comparisons (Klosinska et al ., ).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations